2016
DOI: 10.1017/s1751731116000318
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for placental compensation in cattle

Abstract: Prenatal development is known to be extremely sensitive to maternal and environmental challenges. In this study, we hypothesize that body growth and lactation during gestation in cattle reduce nutrient availability for the pregnant uterus, with consequences for placental development. Fetal membranes of 16 growing heifers and 27 fully grown cows of the Belgian Blue (BB) breed were compared to determine the effect of body growth on placental development. Furthermore, the fetal membranes of 49 lactating Holstein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Placental development responds to both fetal signals of nutrient demand and maternal signals of nutrient availability and, by adapting its phenotype, can regulate the distribution of available resources (Fowden et al, 2006b;Fowden and Moore, 2012). In a previous study by the authors on fetal membranes in Holstein Friesian (HF) and Belgian Blue (BB) cattle, parity of the dam and birth season were revealed to affect the placental phenotype (Van Eetvelde et al, 2016). More specifically, two adaptive mechanisms are seen, i. e. an increase in number of cotyledons (in growing BB dams) and an increase in cotyledonary surface (in lactating HF cows and summer placentas).…”
Section: Placenta and Newborn Calfmentioning
confidence: 99%
“…Placental development responds to both fetal signals of nutrient demand and maternal signals of nutrient availability and, by adapting its phenotype, can regulate the distribution of available resources (Fowden et al, 2006b;Fowden and Moore, 2012). In a previous study by the authors on fetal membranes in Holstein Friesian (HF) and Belgian Blue (BB) cattle, parity of the dam and birth season were revealed to affect the placental phenotype (Van Eetvelde et al, 2016). More specifically, two adaptive mechanisms are seen, i. e. an increase in number of cotyledons (in growing BB dams) and an increase in cotyledonary surface (in lactating HF cows and summer placentas).…”
Section: Placenta and Newborn Calfmentioning
confidence: 99%
“…As dairy cattle management is characterized by features such as pregnancy at a young age in primiparous animals and lactation during gestation in multiparous animals, we focused on these typical maternal factors. These features are particularly important as both growth and lactation have recently been shown to significantly affect gross placental traits when coinciding with gestation (Van Eetvelde et al., ). As only the foetal portion of the placental tissue was available for examination, the potential impact of certain maternal factors on the maternal placental tissue could not be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have demonstrated that young age at first gestation and a high level of milk yield during gestation in multiparous dams both reduce intrauterine foetal development, probably by diverting a significant proportion of nutrients to dam growth and milk production (Kamal et al., ). Subsequently, we have demonstrated that both growth and lactation during gestation have a significant impact on gross placental morphology in cattle (Van Eetvelde et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Although other factors may also influence the rate of growth, the above listed are the underlying drivers of any animal's growth. Changes in maternal nutrition during early gestation have been found to influence placental development (Funston et al 2010;Van Eetvelde et al 2016), which sets the foundation for further development of the fetus. However, any related impairment of fetal development, including development of the gastrointestinal tract and respiratory system, does not appear to have long-term effects on steer growth and health.…”
mentioning
confidence: 99%
“…Therefore, maternal nutrition during this mid-tolate gestation period could potentially have long term effects on the carcass. Recent research, on the other hand, suggests that deleterious effects associated with these processes could be lessened through compensatory growth during the remainder of the prenatal stage (Long et al 2010;Duarte et al 2013a;Van Eetvelde et al 2016). This discord in the literature highlights that the relationship A survey conducted across Canada found that on average, feed costs were the greatest component of expenses sustained by livestock operations (Lachapelle 2014).…”
mentioning
confidence: 99%